2012
DOI: 10.1021/la2050493
|View full text |Cite
|
Sign up to set email alerts
|

Microgel Adhesives for Wet Cellulose: Measurements and Modeling

Abstract: Nanostructured adhesive layers were prepared by adsorbing and/or grafting polyvinylamine (PVAm) onto carboxylated poly(N-isopropylacrylamide) (PNIPAM) microgels that were then assembled between layers of wet oxidized cellulose. The wet delamination force was measured as functions of PVAm content, PVAm molecular weight, coverage (mass adhesive/joint area), and the distribution of carboxyl groups in the PNIPAM microgels. The use of microgels is attractive because simple physical adsorption onto the cellulose sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 25 publications
3
29
0
3
Order By: Relevance
“…Finally, from a mechanistic perspective, the reduced microgels represent a limiting case of near zero cross-link density when considering the influence of microgel cross-linking on adhesion. Based on our previous modeling, supported by experiments, we argued that the delamination force increases with decreasing cross-link density. , This is because only a narrow band of microgels near the peel front support the peeling load, see Figure . The width of this band increases with increasing microgel extensibility, resulting in more microgels sharing the load.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Finally, from a mechanistic perspective, the reduced microgels represent a limiting case of near zero cross-link density when considering the influence of microgel cross-linking on adhesion. Based on our previous modeling, supported by experiments, we argued that the delamination force increases with decreasing cross-link density. , This is because only a narrow band of microgels near the peel front support the peeling load, see Figure . The width of this band increases with increasing microgel extensibility, resulting in more microgels sharing the load.…”
Section: Discussionmentioning
confidence: 67%
“…In this work, we have chosen poly­( N -isopropylacrylamide) (PNIPAM) copolymer microgels as degradable supporting particles because we have much experience controlling their properties. For example, we have shown that commercial polyvinylamine (PVAm) strongly adsorbs onto nonlabile, PNIPAM carboxylated microgels . The PVAm coated microgels function as good wet cellulose adhesives, particularly with rough cellulose surfaces where coated microgels give much thicker adsorbed layers resulting in better contact between two rough surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, for more academic and mechanistic studies, wet-peeling has proved to be useful in evaluating more exotic joint structures such as layer-by-layer (Feng et al 2009), microgels (Wen and Pelton 2012), and colloidal polyelectrolyte complexes (Feng et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] A number of groups have studied MG particles in the presence of polyelectrolytes. [30][31][32][33][34] Diez-Pascual and Wong 31 studied anionic poly(N-isopropylacrylamide-co-methacrylic acid) (PNIPAM-co-MAA) MGs and deposited layers of polycation or polyanion to build up polyelectrolyte layers on their particles. Kleinen et al 23,32,35 studied the binding of poly(diallydimethylammoniumchloride) (PDADMAC) to PNIPAM-co-MAA MGs.…”
Section: Introductionmentioning
confidence: 99%